Cardioprotective Effects of Sodium-glucose Cotransporter 2 Inhibitors Regardless of Type 2 Diabetes Mellitus: A Meta-analysis - Sousa,Lucas Silva (2022)
Abstract Background: Type 2 diabetes mellitus (T2DM) is an independent risk factor for cardiovascular impairment, increasing the rates of atherosclerotic and non-atherosclerotic events. Additionally, adverse kidney events are directly linked with T2DM and cardiovascular diseases. In this context, the sodium-glucose cotransporter 2 inhibitors (SGLT2i) have demonstrated both cardioprotective and renoprotective effects in patients with or without T2DM. Therefore, the present meta-analysis aims to evaluate cardiovascular outcomes involving SGLT2i as monotherapy or other add-on antidiabetic agents (ADA) in patients with or without T2DM. Objetive: The present meta-analysis aims to evaluate cardiovascular outcomes involving SGLT2i as monotherapy or add-on other ADA in patients with or without T2DM. Methods: The entrance criteria to SGLT2i studies were: describing any data regarding cardiovascular effects; enrolling more than 1,000 participants; being approved by either the FDA or the EU, and having available access to the supplementary data. The trial had to exhibit at least one of the following results: major adverse cardiovascular events (MACE), cardiovascular death or hospitalization for heart failure, cardiovascular death, hospitalization for heart failure, renal or cardiovascular adverse events, or non-cardiovascular death. The significance level of 0.05 was adopted in the statistical analysis. Results: Nine trials with a total of 76,285 participants were included in the meta-analysis. SGLT2i reduced MACE (RR 0.75, 95% CI [0.55-1.01]), cardiovascular death or hospitalization for heart failure (RR 0.72, 95% CI [0.55-0.93]), cardiovascular death (RR 0.66, 95% CI [0.48-0.91]), hospitalization for heart failure (RR 0.58, 95% CI [0.46-0.73]), renal or cardiovascular adverse events (RR 0.55, 95% CI [0.39-0.78]), and non-cardiovascular death (RR 0.88, 95% CI [0.60-1.00]). Conclusions: Conjunction overall data suggests that these drugs can minimize the risk of cardiovascular events, thus decreasing mortality in patients, regardless of the presence of T2DM.